The Effect of Investment, Unemployement, Inflation, Human Development and Government Expenditure on Economic Growth and Poverty in Indonesia - Oktavia, Shintami; Matondang, Muhammad Alhasymi; Handriyani, Richna; Amar, Syamsul (Journal Economy and Currency Study (JECS), 2024)
This study aims to determine the effect of investment, unemployment, inflation, human development and government spending on economic growth and poverty in Indonesia. This study uses panel data for 2012-2021 in 33 provinces, which is analyzed using a simultaneous equation approach using the Two Stage Least Square (2SLS) method and to look at the mutual relationships between endogenous variables using the Granjer model (Causality Test). This research uses hypothesis testing, namely the F test and t test. The results of this research; First, equation 1. The influence of investment, unemployment and inflation together have a significant effect on economic growth. Partially, first, poverty has no significant effect on economic growth. Second, investment has no significant effect on economic growth. Third, unemployment has a significant effect on economic growth. Fourth, inflation has a significant effect on economic growth. Then equation 2 the effects of inflation, human development and government spending together have a significant effect on poverty. Partially, first, economic growth has no significant effect on poverty. Second, inflation has a significant effect on poverty. Third, human development has a significant effect on poverty. Fourth, government spending has no significant effect on poverty. The result of Granjer's model (causality test) is that there is no reciprocal relationship between economic growth and poverty.